A new flexible DBD device for treating infected wounds: in vitro and ex vivo evaluation and comparison with a RF argon plasma jet. (24th December 2015) - Boekema, B K H L; Vlig, M; Guijt, D; Hijnen, K; Hofmann, S; Smits, P; Sobota, A; van Veldhuizen, E M; Bruggeman, P; Middelkoop, E
Abstract: Cold plasma has been shown to provide a promising alternative antimicrobial treatment for wound healing. We developed and tested a flexible surface dielectric barrier discharge (DBD) and compared it to an argon gas based plasma jet operated remotely with a distance between plasma plume and sample of 8 mm. Tests were conducted using different models: on cultured cells, on ex vivo human skin and on bacteria ( Pseudomonas aeruginosa ) (on agar, in suspension, in collagen/elastin matrix or on ex vivo human skin), allowing us to directly compare bactericidal with safety aspects under identical conditions. Both plasma devices were highly efficient when used on bacteria in non-buffered solutions, but DBD was faster in reaching the maximum bacterial reduction. Treatment of bacteria on intact skin with DBD resulted in up to 6 log reductions in 3 min. The jet was far less efficient on intact skin. Even after 8 min treatment no more than 2 log reductions were obtained with the jet. Treatment of bacteria in burn wound models with DBD for 6 min resulted in a 4.5 log reduction. Even when using DBD for 6 min on infected burn wound models with colonizing or biofilm phase bacteria, the log reductions were 3.8 or 3.2 respectively. DBD plasma treatment for 6 min did not affect fibroblast viability, whereas a treatment for 8 min was detrimental. Similarly, treatment with DBD or plasma jet for 6 min did also not affect the metabolic activity of skin biopsies. After treatment for 8 min with DBD or plasma jet, 78% or 60% of activity in skin biopsies remained, respectively. Multiple treatments of in vitro burn wound models with surface DBD for 6 min or with plasma jet for 8 min did not affect re-epithelialization. With the flexible surface DBD plasma strip we were able to quickly inactivate large numbers of bacteria on and in skin. Under the same conditions, viability of skin cells or re-epithelialization was not affected. The DBD source has potential for treating larger wound areas.